UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MASA PANDEMI COVID 19 DI SMK NEGERI 1 KLABANG: SMK NEGERI 1 KLABANG - PAIMIN (Dewan Pendidikan Bondowoso, 2022)
The purpose of this action research is to 1) Find out the principal's efforts in improving the ability of teachers to plan learning during the Covid 19 pandemic at SMK Negeri 1 Klabang 2). Knowing the efforts of the principal in improving the ability of teachers to carry out learning during the COVID-19 pandemic at SMK Negeri 1 Klabang 3). Knowing the efforts of school principals in improving the ability of teachers to evaluate learning during the COVID-19 pandemic at SMK Negeri 1 Klabang. The type of research used in this study is a type of qualitative research. This qualitative research is descriptive in the form of speech and writing that can be observed from the subject itself (Arif Furchan, 1992). While the approach in this research is a case study. Case study research is technically a research conducted intensively, in detail, and in depth on a particular symptom or phenomenon in an organization, institution (Suharsimi Arikunto. 2002). The presence of researchers, In qualitative research, the presence of researchers themselves is the main data collection tool (Suharsimi Arikunto, 2002) So that the presence of researchers themselves in the field is needed in achieving optimal research. Therefore, in this study, researchers must directly conduct research in the field This research was carried out at SMK Negeri 1 Klabang Bondowoso which is located at Jalan Blimbing NO. 12, Klabang District, Bondowoso Regency, for 3 months, from September to November 2021. The sources of data in this study are: 1). Primary Data and 2) Secondary Data Data collection techniques Data collection techniques are very important in ensuring the credibility of information in conducting research. In qualitative research, data collection is very important in supporting the success of researchers. The data collection techniques of this research consist of 1). Observation, 2). Interviews, and 3). Documentation Studies. While the data analysis techniques used in this research are 1). Data Reduction, 2). Data Presentation and 3). Withdrawal of Conclusion Conclusions, 1). The principal's efforts to improve teacher performance in making lesson plans are principals using efforts to control and supervise teacher performance so that the control of educational activities in schools is in line with the goals that have been set. 2). The principal's efforts to improve teacher performance in the implementation of learning are by sending teachers to attend training, upgrading, workshops, workshops, and seminars so that the implementation of distance learning can take place optimally according to ongoing conditions. 3). The principal's efforts to improve teacher performance in learning evaluation are by controlling so that all activities in the evaluation are in accordance with the previous series